Autologous protein solution: a promising solution for osteoarthritis?. Issue 9 (September 2021) - Bin Abd Razak, Hamid Rahmatullah; Chew, Daniel; Kazezian, Zepur; Bull, Anthony M.J.
Abstract : Osteoarthritis (OA) is a global health issue with myriad pathophysiological factors and is one of the most common causes of chronic disability in adults due to pain and altered joint function. The end stage of OA develops from a destructive inflammatory cycle, driven by the pro-inflammatory cytokines interleukin-1β (IL-1β) and tumour necrosis factor alpha (TNFα). Owing to the less predictable results of total knee arthroplasty (TKA) in younger patients presenting with knee OA, there has been a surge in research evaluating less invasive biological treatment options, one of which is autologous protein solution (APS). APS is an autologous blood derivative obtained by using a proprietary device, made of APS separator, which isolates white blood cells (WBCs) and platelets in a small volume of plasma, and APS concentrator, which further concentrates platelets, WBCs and plasma proteins, resulting in a concentrated solution with high levels of growth factors including the anti-inflammatory mediators against IL-1β and TNFα. A single intraarticular injection of APS appears to be a promising solution for treatment of early-stage OA from current evidence, the majority of which comes from preclinical studies. More clinical studies are needed before APS can be widely accepted as a treatment modality for OA. Cite this article: EFORT Open Rev 2021;6:716-726. DOI: 10.1302/2058-5241.6.200040